2019
DOI: 10.1155/2019/9103412
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Atypical Fracture of the Ulnar Diaphysis by Open Reduction and Internal Fixation with Teriparatide

Abstract: Atypical fractures commonly arise in the subtrochanteric region or the femoral shaft, whereas those of the upper extremities are rare. Only 15 fractures in 13 patients have been described in the English literature. The management of such fractures has not been established. We describe a patient with an atypical fracture of the ulnar diaphysis, which required revision surgery to achieve the union of the fracture site. Teriparatide together with low-intensity pulsed ultrasound contributed to bone healing. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
0
9
0
1
Order By: Relevance
“…Additional treatment included use of bone graft, dual plate, LIPUS, and administration of teriparatide. The outcomes of additional treatment and mean duration of follow-up are summarized in Table 1 [6][7][8][9][10][11][12][13][14][20][21][22]. Details of drilling and decortication are not included in Table 1 owing to the very few reports that described drilling and decortication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional treatment included use of bone graft, dual plate, LIPUS, and administration of teriparatide. The outcomes of additional treatment and mean duration of follow-up are summarized in Table 1 [6][7][8][9][10][11][12][13][14][20][21][22]. Details of drilling and decortication are not included in Table 1 owing to the very few reports that described drilling and decortication.…”
Section: Discussionmentioning
confidence: 99%
“…Atypical fracture of the ulna due to SSBT is a rare entity [ 6 ]; therefore, there is no standardized treatment strategy. In addition, widely variable treatment outcomes have been described in previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The papers included in the review are reported by category in Table 2. (15)(16)(17)25,26,(29)(30)(31)(32)(33) 205 Bone substitutes (41,42,45,46,48) 331 Growth factors (53,(55)(56)(57)(58) 615 Cell therapies (66,69,73) 69 Pharmacological therapy (97)** (98)(99)(100)(101)(102)(103)(104)(105)(107)(108)(109)(110)(111)(112)(113)(114) 110 ** Systematic review including case series and case reports.…”
Section: Resultsmentioning
confidence: 99%
“…Shimada et al [102] and Ito et al [103] reported the successful treatment of three cases of ulnar atypical fracture, with internal fixation, teriparatide and low-intensity pulsed ultrasound.…”
Section: Parathormone Analoguesmentioning
confidence: 99%